The relationship between hand hygiene practices and nasal Staphylococcus aureus carriage in healthcare workers - Genc, Ozlem; Arikan, Inci (La Medicina del Lavoro, 2020)
Background: The nasal carriage rate of Staphylococcus aureus in healthcare workers (HCWs) is higher than the general population. Their hands serve as vectors for transmitting S.aureus colonized in the nose to patients. Objectives: To determine the rate of nasal S.aureus carriage and methicillin resistance in HCWs and to evaluate the relationship between carriage and personal risk factors and hand hygiene behaviors. Methods: The questionnaire included questions about sociodemographic characteristics, occupational and personal risk factors for S.aureus carriage, the “Hand Hygiene Belief Scale (HHBS),” and “Hand Hygiene Practices Inventory (HHPI)”. Nasal culture was taken from all participants. Presence of S.aureus, methicillin and mupirocin resistance were investigated in samples. Results: The study was carried out with 269 HCWs. The prevalence of S.aureus carriage was 20.1% (n:54). Among 54 S.aureus carriers, only one person had MRSA (0.37%). All S.aureus isolates were susceptible to mupirocin. S.aureus carriage was found to be significantly lower in the smoker group (p:0.015) and in the personnel wearing gloves during the procedures of each patient (p:0.002). S.aureus culture positivity was found to decrease significantly with increasing handwashing frequency (p:0.003). The mean HHPI score was higher in women (p:0.001). The mean HHPI score was lower in the group with nasal carriers than in non-carriers (p:0.176). Conclusion: The knowledge of hand hygiene practices, high frequency of handwashing, and wearing different gloves during the procedure of each patient decrease S.aureus nasal carriage in HCWs. In addition mupirocin is still effective in nasal S.aureus carriers.